Environmental Management Model for Tanjung Benoa Tourism Attraction - I Nyoman Sudipa; Nyoman Utari Vipriyanti; Putu Edi Yastika (Jurnal Ilmu Lingkungan, 2025)
Tanjung Benoa Tourism Object is a leading tourism object in Badung Regency. The increasing number of tourists and residents has caused pressure on the water area, resulting in a decline in environmental quality. In sustainable tourism management, it is necessary to formulate an environmental management model developed based on local wisdom. The research method uses the Interpretative Structural Modeling (ISM) system approach to formulate an environmental management model for Tanjung Benoa tourism objects through interviews and focus group discussions involving community leaders and experts to formulate elements and sub-elements. The elements selected are (1) main constraints, (2) program objectives, (3) affected community sectors, (4) desired changes, and (5) the need for implementation of water pollution control programs. The results and findings of the study indicate that: (1) the main constraints in managing tourism objects in Tanjung Benoa are limited human resources and weak financial support; (2) The main targets of the program are to improve environmental quality, maintain environmental carrying capacity, reduce land conversion, change environmental behavior and awareness, and realize sustainable tourism; (3) The main influence is the government; (4) The main changes desired are environmental cleanliness, reduced environmental violations, the formation of environmental partnerships, sustainable tourism and environmental management, and increased awareness of the business world and the community; (5) The need for implementing the main program is budget availability. The recommended environmental management model is management that is implemented comprehensively and involves stakeholders in a participatory manner.